Reliability Estimation of Time-Dependent Stress-Strength system for different Distributions - T. Sumathi Uma Maheswari, K. Sandhya Rani, P. Ashok, M. Tirumala Devi (International Journal of Advanced Science and Technology, 2020)
In this article, general expression for reliability of n-cycle time-dependent stress-strength system has been derived. The estimation of Reliability of time-dependent Stress-Strength system for n number of cycles is obtained. Reliability is estimated by simulation technique for random fixed stress which follow Lindley distribution and random-independent strength which follow exponential distribution The maximum likelihood estimation method was used in estimating the parameters and a simulation study was carried out to examine the performance and accuracy of the maximum likelihood estimation of the parameters. The numerical values are generated by mat lab.